Patients' Perspectives on Emergency Department COVID-19 Vaccination and Vaccination Messaging Through Randomized Vignettes. (July 2022) - Waxman, Michael J.; Ray, Maile; Schechter-Perkins, Elissa M.; Faryar, Kiran; Flynn, Karen Coen; Breen, Mandi; Wojcik, Susan M.; Berry, Fiona; Zheng, Amy; Ata, Ashar; Lerner, E. Brooke; Lyons, Michael S.; et al.
Objectives: Emergency departments (EDs) could play an important role in the COVID-19 pandemic response by reaching patients who would otherwise not seek vaccination in the community. Prior to expanding COVID-19 vaccination to the acute care setting, we assessed ED patients' COVID-19 vaccine status, perspectives, and hypothetical receptivity to ED-based vaccination. Methods: From January 11 through March 31, 2021, we conducted a multisite (Albany Medical Center, Boston Medical Center, Buffalo General Hospital, University of Cincinnati Medical Center, and Upstate Medical Center), cross-sectional survey of ED patients, with embedded randomization for participants to receive 1 of 4 vignette vaccination messages (simple opt-in message, recommendation by the hospital, community-oriented message, and acknowledgment of vaccine hesitancy). Main outcomes included COVID-19 vaccination status, prior intention to be vaccinated, and receptivity to randomized hypothetical vignette messages. Results: Of 610 participants, 122 (20.0%) were vaccinated, 234 (38.4%) had prior intent to be vaccinated, 111 (18.2%) were unsure as to prior intent, and 143 (23.4%) had no prior intent to be vaccinated. Vaccine hesitancy (participants who were vaccine unsure or did not intend to receive the vaccine) was associated with the following: age <45 years, female, non-Hispanic Black, no primary health care, and no prior influenza vaccination. Overall, 364 of 565 (64.4%; 95% CI, 60.3%-68.4%) were willing to accept a hypothetical vaccination in the ED. Among participants with prior vaccine hesitancy, a simple opt-in message resulted in the highest acceptance rates to hypothetical vaccination (39.7%; 95% CI, 27.6%-52.8%). Conclusions: EDs have appropriate patient populations to initiate COVID-19 vaccination programs as a supplement to community efforts. A simple opt-in approach may offer the best messaging to reach vaccine-hesitant ED patients.